Upaya Mengembangkan Komunikasi Interpersonal Antara Guru dengan Siswa untuk Meningkatkan Efektifitas Kegiatan Belajar Mengajar dan Hasil Belajar - Rahayu, Sri (Jurnal Pendidikan Dasar, 2023)
Research on efforts to develop interpersonal communication between teachers and students to improve the effectiveness of teaching and learning activities and student learning outcomes at SDN 2 Kedungjati, Kedungjati sub-district, Grobogan district for the 2018/2019 school year. The subjects of this study were teachers and students of SDN 2 Kedungjati. The results showed that the application of intensive learning guidance and counseling through effective interpersonal communication between teachers and students had a positive impact on improving teacher performance. The teacher's ability to manage learning in each cycle has increased. There is a significant increase in student activity in the learning process which can ultimately improve learning outcomes